Embedded Barriers and Impending Costs: The Relationship between Disability, Public Schooling, Post-Secondary Education, and Future Income Earnings - Parekh, Gillian; Brown, Robert S.; Walters, David; Collis, Ryan; Jacob, Naleni (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2025)
In Canada, access to post-secondary education (PSE), which includes university, college, or apprenticeship programs, is becoming ever more important in terms of securing future employment, long-term health, and economic security. Kirby (2009) points to Canada’s universal level of PSE access; however, also notes how access for students with disabilities continues to be more limited. With a focus on education, we grounded this study in critical disability theory to consider how disability is constructed and produced through social, environmental, and economic factors. This study built on earlier research that examined students’ graduation from post-secondary education, primarily university and college, and explored disabled students’ access to post-secondary education and their future earnings following PSE participation. Using a unique linked dataset between school board and federal data, our study revealed that disabled students are almost twice as likely to not access post-secondary education compared to their non-disabled peers. Across disability status, the outcomes of post-secondary credentials do not appear to result in future income parity, suggesting persistent ableism within the workforce.